Energetic evaluation of hydrogen storage in metal hydrides. (25th May 2016) - Adametz, Patrick; Müller, Karsten; Arlt, Wolfgang
Summary: Metal hydrides are considered as promising candidates for hydrogen storage as they exhibit higher energy densities than compressed gas storage storages. This study represents a theoretical thermodynamic analysis of metal hydride‐based hydrogen storage systems, focusing mainly on the energy demand to operate the storage system and the resulting efficiency. The main energy demand occurs during hydrogen release. This energy demand is composed of three contributions: the heat required to heat the hydride up to desorption temperature, the heat of reaction and the work of compression to reach the targeted outlet pressure. A sensitivity analysis was performed to demonstrate the impact of several parameters, for example, heat of reaction and hydrogen uptake on the energy balance. The most influential parameter is the heat of reaction. The hydrogen uptake does not have a noticeable influence as long as it is not too low. Several possibilities to improve the efficiency of the storage system are discussed (heat integration and the application of a heat storage system). Heat integration can significantly improve the overall efficiency, whereas the application of a heat storage system does not seem realistic. Compared with other hydrogen storage technologies, metal hydrides can feature higher efficiencies than low‐temperature hydrogen storage concepts, for example, liquefied or cryo‐adsorbed hydrogen. The efficiencies of a metal hydride storage system are similar to those reached with a system based on liquid organic hydrogen carriers. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This study presents an overall thermodynamic analysis of the storage of hydrogen in metal hydrides, focusing on the impact of material properties and process conditions on the energy balance. Main impact factors on the energy balance are heat of reaction and desorption pressure; hydrogen uptake does not have a notable influence as long as it is higher than 5%. If used as electricity storage, efficiencies between 6 and 29 % are possible, depending on the heat delivery and heat integration.